The Effectiveness of Local Government in Providing Legal Aid in Bali - I Putu Rasmadi Arsha Putra; Putu Devi Yustisia Utami; Ni Kadek Rista Puspa Sari; Ni Wayan Luh Duti Ari Anggreni (Sociological Jurisprudence Journal, 2025)
This study will investigate the role of local governments in providing legal aid to underprivileged communities in Bali and evaluate the effectiveness of legal aid for underprivileged communities in Bali. This study uses empirical legal research with primary and secondary data analyzed using qualitative methods. From this study, it can be seen that the role of local governments in providing legal aid to underprivileged communities in Bali is still ineffective. Local regulations on legal aid have not been established in all districts in Bali. Local regulations are a manifestation of the seriousness, obligation, and political will of each local government in carrying out its duties towards the people in its region who are in need. The ineffective provision of legal aid to the underprivileged in Bali is influenced by five factors, namely legal factors, law enforcement factors, infrastructure and facility factors, community environment factors, and community cultural factors. Therefore, in addressing such conditions, proactive efforts are needed from local governments to provide legal aid to the underprivileged by improving the legal aid system, starting from regulations, empowering law enforcement agencies, conducting structured and planned outreach, and striving to create a more effective and modern legal aid mechanism.